British or American English? : a handbook of word and grammar patterns - Algeo, John (Studies in English language., 2006)
This is a clearly organized guide to the differences - and similarities - between the grammar of British and American speakers of English. Assuming no prior knowledge of linguistics, and containing extensive quotations from real-life English on both sides of the Atlantic, it provides an accessible account of contemporary English in use.